Traces of Kantian Ethics in the Presciptivism of R. M. Hare - Baranova, Jūratė (Problemos, 2004)
The most open to Kant of all metaethicians is Richard Hare, who, in contrast to intuitivists, is not denying his theoretical debt to him. It is Hare who notices the parallel between Hume’s remark about the possibility to see no distinction between fact and norm in moral discourse and the Kantian distinction between heteronomy and autonomy. Hume according his interpretation with this insight comes very close to Kant. On the other side, Hare thinks that every moral judgement is prescription. It is imperative. And the idea to ground moral thinking with imperativeness in Hare’s moral philosophy reaches from Kant as well. Besides, what is the most Kantian peculiarity of Hare’s moral philosophy – is the basement of moral thinking on the principle of universalizability. Universality is the criterion which allows him to make a distinction between moral prescriptions from other types of prescriptions. On the other hand, acknowledging very great debt to Kant, Hare tries to avoid the Kantian exegesis. He does not see moral principles as existing antecedently. In his moral philosophy Hare is trying to unite some aspects of Aristotle's, some aspects of Kant's ethics. He does not oppose them each other. On the other hand, Hare distances himself from Kant trying to find the way of smoothing the opposition between fact and norm. But nevertheless, in opposition to all previous kinds of metaethics, Hare’s moral philosophy is based on the same grounds as Kantian ethics was: he reasons in rationalistic perspective stemming from Kant and believes that logic is able – has power – to prevent this reasoning man from moral mistakes.
Keywords: prescriptivism; Hare; fact and norm; Kant; acrasia